Comparison of gas chromatography detectors and its application in food analysis - Yurika Sugiharto; Evelyn Natania; Sherlin Angelina Febriyanti; Oki Krisbianto (Universitas Veteran Bangun Nusantara, 2022)
Gas Chromatography (GC) is an instrument used for analyzing gaseous compounds based upon differences of boiling point and polarity. The mobile phase of GC is an inert (unreactive) gas. GC consists of several components, one of them is a detector. Detector provides an electronic signal that is recorded, and component concentration shown in the chromatogram. A detector has interrelated properties to the other. The properties of the detector are considered under three main headings: (1) types of detector, (2) sensitivity, and (3) ease of operation. Ideal detector for one application is not necessarily ideal for another application. Application of GC coupled with a detector in food analysis are also informed. Detectors that are discussed are Thermal Conductivity Detector (TCD), Flame Ionization Detector (FID), Electron Capture Detector (ECD), and Mass Spectrometer (MS).